Gender Disparities on Access to Care and Coronary Disease Management - Vasiljevic-Pokrajcic, Zorana; Krljanac, Gordana; Lasica, Ratko; Zdravkovic, Marija; Stankovic, Sanja; Mitrovic, Predrag; Vukcevic, Vladan; Asanin, Milika (Current Pharmaceutical Design, 2021)
Mortality decline in women to a lesser extent than in men with coronary artery disease (CAD) has provoked a bigger interest in some already existing dilemmas and questions. Many studies carried out in the past three decades did not provide us with precise conclusions. Moreover, various challenges in the prevention, diagnosis, treatment and outcome of CAD in women are still remaining. The meta-analysis and the systematic review conducted in the last years have offered novel approaches to understanding CAD gender disparities in access to care and coronary disease management in women, but women are more likely to experience less favorable short- and long-term outcomes than men do. The reasons for these findings should lie in several known segments in the CAD pathophysiological mechanisms different in women and ultimately leading to a lower quality of care. Clinical presentation in women, which is often characterized by atypical chest pain and a higher prevalence of non-obstructive CAD when evaluated invasively, places women to the false-negative diagnosis of CAD and influences inadequate access to care. Clinical presentation and diagnostic methods, as well as the appropriate treatment options insufficiently examined in women, need to be better defined. The traditional CAD risk factors have a greater impact on women than on men. Unique CAD risk factors only seen in women, have recently been recognized with more attention. However, it is important to note that even in women with obstructive CAD and typical clinical presentation, invasive therapy and pharmacologic therapy are not always implemented as recommended by guidelines as in men. Women are underrepresented in CAD trials, and in current guidelines, gender differences in CAD management have not yet been justified. The underestimation of the risk of CAD in women, followed by its underdiagnosis and undertreatment, might be one of the reasons for a worse prognosis in women in comparison with men.
Keywords: women